2003
DOI: 10.1046/j.1472-765x.2003.01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Shiga toxin-producing Escherichia coli (STEC) and enteropathogenic Escherichia coli (EPEC) from calves and lambs with diarrhoea in India

Abstract: Aims: To determine the prevalence and molecular characteristics of Shiga toxin-producing Escherichia coli (STEC) and enteropathogenic E. coli (EPEC) in calves and lambs with diarrhoea in India. Methods and Results: Faecal samples originating from 391 calves and 101 lambs which had diarrhoea were screened for presence of E. coli. A total number of 309 (249 bovine and 60 ovine) E. coli strains were isolated. A total of 113 bovine and 15 ovine strains were subjected to multiplex polymerase chain reaction (m-PCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
53
4
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 23 publications
21
53
4
2
Order By: Relevance
“…in small ruminants from Turkey (Gokce et al 2010) and other states (Wani et al 2004), however, research on classification of enterovirulent E. coli and its virulence genes is limited. Recent studies have reported (Wani et al 2003;Bhat et al 2008;Bandyopadhyay et al 2011), the existence of at least one virulence gene in 41%, 36.7%, and 32.6% of E. coli isolates, respectively. In our study we found at least one virulence gene for EHEC or STEC, EPEC, ETEC, EIEC, and EAEC among 36.4% of the isolates.…”
Section: Resultsmentioning
confidence: 99%
“…in small ruminants from Turkey (Gokce et al 2010) and other states (Wani et al 2004), however, research on classification of enterovirulent E. coli and its virulence genes is limited. Recent studies have reported (Wani et al 2003;Bhat et al 2008;Bandyopadhyay et al 2011), the existence of at least one virulence gene in 41%, 36.7%, and 32.6% of E. coli isolates, respectively. In our study we found at least one virulence gene for EHEC or STEC, EPEC, ETEC, EIEC, and EAEC among 36.4% of the isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Trend on the prevalence of E.coli in both diarrhoeic and non diarrhoeic adult pigs and piglets as shown in (Figure 2) The present finding is similar with the findings of Sharma et al, (2004) who also reported highest (94.52%) prevalence of E.coli in comparision to non-diarrhoeic calves. Hussain and Saikia (2000) and Wani et al, (2003) however isolated E.coli from all cases of calf diarrhea. Shah and Jhala (1990) isolated E.coli from 61.2% of diarrhoeic calves.…”
mentioning
confidence: 99%
“…Briefly, bacterial strains, grown overnight in nutrient broth at 37 o C, were pelleted by centrifugation at 10000 rpm at 4 o C for 10 min (Hermle Labortechnik GmBH, Germany), and resuspended in 200 µL of sterile distilled water. Bacteria were lysed by boiling for 10 min; lysates were centrifuged as described above and 200 µL of the supernatant were utilized as the polymerase chain reaction (PCR) template [18]. The reaction was performed in a total volume of 25 µL composed of 12.5 µL of EmeraldAmpGT PCR Master Mix, 1 µL F-STa, 1 µL R-STa, 6 STa was produced and purified according to Aref and Saeed [19].…”
Section: Purification and Characterization Of Native Sta From Etecmentioning
confidence: 99%